Supervisory practices for intrinsic motivation of doctoral students: a self-determination theory perspective - Kumar, Vijay; Kaur, Amrita (2019)
Aim/Purpose The quality, degree of effort and persistence required in doctoral studies can be sustained through intrinsic motivation. Despite the critical role of motivation, studies that examine ways to promote doctoral students’ motivation are lacking.This study, drawing on the self-determination theoretical (SDT) framework, aims to offer advice for supervisory practices to facilitate the satisfaction of three basic psychological needs- autonomy, competence and relatedness of doctoral students’ motivation. The focus was on the experiences of the doctoral candidates who participated in this study. Background Prior studies have established that creating environment and ways that lead to satisfaction of three basic psychological needs are capable of producing optimal outcomes. Based on that assumption the current study explores the ways in which supervisory practices lead to satisfaction of the three needs. Methodology The study adopted a qualitative approach and used the experience sampling method to collect data from 11 full-time doctoral students from a research intensive university in New Zealand. In total, 72 entries that captured students’ real-time psychological experience of supervision in a repeated manner were used to analyse the data. Contribution It proposes theory driven practices/guidelines for supervisors to adopt for effective supervisory practices for intrinsic motivation of doctoral students. Findings Thematic analysis guided by the research question revealed that to have students experience autonomy support the supervisors must respect students’ research